The Impact of Farmer Families' Communication in Compliance Nutritional Needs among Toddlers - Alvita Galuh Nurprastiwi; Nathasya Alfisyahr Sasongko; Enggal Hadi Kurniyawan; Kholid Rosyidi Muhammad Nur; Alfid Tri Afandi; Dicky Endrian Kurniawan (Health and Technology Journal (HTechJ), 2024)
The nutritional status of a toddler reflects the level of development and welfare of society in a country. Poor nutritional status can lead to wasting, stunting, decreased cognitive ability, or disease susceptibility. Nutritional status can be affected by ineffective communication support. This study aimed to investigate the communication of families in agricultural areas in the fulfillment of toddler nutrition. The method used in this research is to use journal literature studies from Pubmed, ScienceDirect, and Google Scholar with publication years 2020-2024. This research was conducted using 10 journals that have been selected according to the required research criteria. The literature search was conducted using the keywords "Family Communication," "Agricultural Area" AND "Toddler Nutrition." This study's results show that family communication can affect the fulfillment of nutritional needs in toddlers in agricultural areas. Communication with families can increase knowledge about nutrition and family behavior in providing a diet that can improve the nutritional status of toddlers. Parents are in a prime position to help toddlers develop a healthy diet early on. As nurses, we can provide health education to parents to maintain communication with toddlers and monitor their growth, including their nutritional status.